(untitled) (Applied Biological Research, 2014)
Aspergillus niger strain HD-6, isolated from Anand, Gujarat (India), was evaluated for endocellulase enzyme production through solid state fermentation (SSF) using bajra straw as main carbon source. Various cultural conditions such as temperature, pH, moisture content, incubation period, nitrogen source, inoculum age and size, etc. were standardized for optimum enzyme production. Using 3 g bajra straw as sole carbon source maximum endocellulase production from 96 hr old A. niger HD-6 was achieved at pH 5.0, incubation temperature 28°C and moisture content 65% after incubation for 4 days.